Differences Characteristics Patients Diabetes Mellitus Type 2 with and without Coronary Heart Disease - Nindara Citra Aquarista (Jurnal Berkala Epidemiologi, 2017)
Diabetes mellitus is the 3rd highest Non-Communicable Disease (NCD) which causes death in Indonesia. The biggest cause of mortality and morbidity in type 2 diabetes mellitus is coronary heart disease. The incidence of coronary heart disease in diabetes mellitus is relatively high, 65% of people with diabetes mellitus die from coronary heart disease and stroke. This study aims to analyze differences in characteristics in patients with diabetes mellitus type 2 with and without coronary heart disease in the Haji Public Hospital (RSU Haji) in 2016. This study is an observational analytic study with a cross-sectional study design. The subject of the study was the incidence of diabetes mellitus type 2 with and without coronary heart disease who underwent treatment in the outpatient installation of RSU Haji Surabaya in 2016. Samples were taken using the fixed-disease sampling method. The sample size was 42 people. Data analysis was performed using the Chi-square test. The results showed that smoking behavior (p = 0.00; PR = 7.85; 95% CI = 2.09–29.50) and hypertension (p = 0.002; PR = 3.51; 95% CI = 1, 42–8,67) has a significant difference in the incidence of diabetes mellitus type 2 with and without coronary heart disease. It was concluded that smoking behavior and hypertension can lead to complications of coronary heart disease in patients with diabetes mellitus type 2 at RSU Haji Surabaya in 2016. Awareness is needed to conduct routine blood pressure checks and eliminate smoking as prevention of complications of coronary heart disease in people with diabetes mellitus type 2.